Maritime Liens and Ship Mortgages Under Egyptian Law - Mohamed, Abdulla H (Journal of maritime law and commerce, 2020)
The maritime lien on the ship is unique to shipping. To understand its underlying rationale, it is necessary to consider the various characteristics of the ship. The ship is not necessarily always in the immediate possession and control of the owner. It needs necessary expenditures to undertake and continue a maritime adventure. It needs to be navigated or managed professionally. It can cause injury to others. It can change its nationality with ease and can be registered under a flag with which it bears no beneficial link. Throughout its life, the ship can engage various creditors. Therefore, in order for the ship to be an instrument of trade, it needs certain services. There has long been recognition of "creditors of necessity" in the maritime adventure: persons providing essential navigation services to the ship (i.e. master and crew); the person incurring necessary expenditures (i.e. disbursements); persons assisting ships, cargoes, and crews in situations of distress (i.e. salvors); persons suffering injury or loss caused by the ship. These persons have been perceived either as providing fundamental services to the ship or as victims of a maritime tort that must be compensated by the negligent ship. They were deemed to deserve special protection in general maritime law. Therefore, special tools have been devised since the early days to protect persons and property that have come into contact with the ship and have suffered damage or incurred expense thereby. The lien in a maritime context is one such tool.On the other hand, the evolution of the shipbuilding industry makes modern ships a synthesis of all up to date technical and scientific achievements. Thus, the value of such ships is increased to the extent that sometimes they represent a considerable percentage of the assets of even the big shipping companies. A mortgage of a ship is a common way of financing its construction or purchase or to secure a loan.It is worth mentioning here that there are three international conventions focusing on maritime liens and ships' mortgages: the International Convention for the Unification of Certain Rules Relating to Maritime Liens and Mortgages, 1926 (hereinafter referred to as the 1926 Convention); the International Convention for the Unification of Certain Rules Relating to Maritime Liens and Mortgages, 1967 (hereinafter referred to as the 1967 Convention); and the International Convention on Maritime Liens and Mortgages, 1993 (hereinafter referred to as the 1993 Convention). Egypt is not a party to any of these conventions. However, Egypt adopted the provisions of the 1926 Convention into its Maritime Trade Law and the Convention has been the model for the maritime liens and ships' mortgages provisions under the Law.1The purpose of this paper is to examine the provisions and operation of maritime liens and ships' mortgages under Egyptian Maritime Trade Law 1990 (hereinafter referred to as EMTL 1990). In order to properly undertake this task, the paper is divided into two parts. The first part examines the maritime liens, and the second part examines the ships' mortgages.